Logarithmic corrections to the entropy of non-extremal black holes in N $$ \mathcal{N} $$ = 1 Einstein-Maxwell supergravity - Gourav Banerjee (SpringerOpen, 2021)
Abstract We reviewed the field redefinition approach of Seeley-DeWitt expansion for the determination of Seeley-DeWitt coefficients from arXiv:1505.01156 . We apply this approach to compute the first three Seeley-DeWitt coefficients for “non-minimal” N $$ \mathcal{N} $$ = 1 Einstein-Maxwell supergravity in four dimensions. Finally, we use the third coefficient for the computation of the logarithmic corrections to the Bekenstein-Hawking entropy of non-extremal black holes following arXiv:1205.0971 . We determine the logarithmic corrections for non-extremal Kerr-Newman, Kerr, Reissner-Nordström and Schwarzschild black holes in “non-minimal” N $$ \mathcal{N} $$ = 1, d = 4 Einstein-Maxwell supergravity.